The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4103/0972-5229.195701
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patient-ventilator asynchrony during pressure support ventilation and proportional assist ventilation modes in surgical Intensive Care Unit: A randomized crossover study

Abstract: Background:The patient-ventilator asynchrony is almost observed in all modes of ventilation, and this asynchrony affects lung mechanics adversely resulting in deleterious outcome. Innovations and advances in ventilator technology have been trying to overcome this problem by designing newer modes of ventilation. Pressure support ventilation (PSV) is a commonly used flow-cycled mode where a constant pressure is delivered by ventilator. Proportional assist ventilation (PAV) is a new dynamic inspiratory pressure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Comparing patient-ventilator asynchrony between PSV and PAV plus (PAVϩ) in 20 surgical subjects during weaning, Gautam et al 68 found that asynchrony was less common in PSV. The mean number of total asynchronous recorded breaths was 7.05 Ϯ 0.83 during sleep and 4.35 Ϯ 5.62 when subjects were awake in PSV versus 6.75 Ϯ 112.24 and 10.85 Ϯ 11.33, respectively, in PAVϩ, leading them to conclude that PAVϩ was not superior to PSV with respect to cardiorespiratory function.…”
Section: Studies On Pavmentioning
confidence: 99%
“…Comparing patient-ventilator asynchrony between PSV and PAV plus (PAVϩ) in 20 surgical subjects during weaning, Gautam et al 68 found that asynchrony was less common in PSV. The mean number of total asynchronous recorded breaths was 7.05 Ϯ 0.83 during sleep and 4.35 Ϯ 5.62 when subjects were awake in PSV versus 6.75 Ϯ 112.24 and 10.85 Ϯ 11.33, respectively, in PAVϩ, leading them to conclude that PAVϩ was not superior to PSV with respect to cardiorespiratory function.…”
Section: Studies On Pavmentioning
confidence: 99%
“…Most studies on PVA have analyzed patients who were relatively stable or had only one respiratory disorder in a few ventilation modalities (sometimes including cases with neuromuscular blockade) and who were observed for a short period. ( 7 - 9 , 19 , 22 , 23 ) In this study, evaluations were performed for several consecutive days, which represents the real context of the clinical course (day to day) of critically ill patients; consequently, we had a greater probability of detecting PVA.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] Finally, newer mode of ventilation such as proportional-assist ventilation (PAV) has theoretical benefits that may reduce ventilator dyssynchrony, but in small studies to date, similar rate of ventilator dyssynchrony has been seen between PSV and PAV. [ 58 59 ] Thus, there is no clear optimal mode of ventilation to manage ventilator dyssynchrony.…”
Section: Management Of Ventilator Dyssynchronymentioning
confidence: 99%